Age estimates based on aspartic acid racemization for bowhead whales (Balaena mysticetus) harvested in 1998–2000 and the relationship between racemization rate and body temperature. Issue 3 (26th September 2012) - Rosa, Cheryl; Zeh, Judith; Craig George, J.; Botta, Oliver; Zauscher, Melanie; Bada, Jeffrey; O'Hara, Todd M.
Abstract: Fifty‐two eyes were collected and analyzed to estimate ages of 42 bowhead whales using the aspartic acid racemization aging technique. Between‐eye and within‐eye variance components for the ratio of the D and L optical isomers (D/L ratio) were estimated via analysis of variance using multiple measurements from nine whales with both eyes sampled and analyzed. For whales with more than one (D/L)act value, an inverse variance weighted average of the values was used as (D/L)act for the whale. Racemization rate ( k A sp ) and D/L ratio at birth (D/L)0 were estimated using (D/L)act from 27 bowhead whales with age estimates based on baleen or ovarian corpora data and two term fetuses. The estimates were k A sp = 0.977 × 10 −3 /yr and (D/L)0 = 0.0250. The nonlinear least squares analysis that produced these estimates also estimated female age at sexual maturity as ASM = 25.86 yr. SE(age) was estimated via a bootstrap that took into account the SE of (D/L)act and the variances and covariance of k A sp and (D/L)0 . One male exceeded 100 yr of age; the oldest female was 88. A strong linear relationship between k A sp and body temperature was estimated by combining bowhead data with independent data from studies of humans and fin whales. Using this relationship, we estimated k A sp and ASM for North Atlantic minke whales.